Thermal transfer performance of downhole electric heaters for in-situ pyrolysis in tar-rich coal - Tang, Ying; Xiao, Li; Yang, Fan; Wu, Xiaodan; Su, Zhan; Zhang, Yue; Jiang, Shixin; Yang, Peng (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The paper investigates the performance of a large-size helical baffle heater in an in-situ operation using a numerical simulation method. The study reveals that the fluid in the shell retains a spiral flow, and the output flow velocity is higher than in the surrounding area. However, the pitch design is big, resulting in a low-velocity flow zone on the backwind side. At 100 kW and 500 m3/h, the fluid flow is turbulent. At 50 kW and 200 m3/h, the fluid remains laminar. As the flow rate rises, the pressure of tar-rich coal formation grows dramatically. The wall temperature exhibits a spiral plunger at the inlet, but the bottom temperature is symmetrically distributed. Under low power and flow, Reynolds number change has a greater impact on the combination of Nusselt and Prandtl numbers. The wellbore experiences higher thermal loads during downhole heating, dramatically increasing the possibility of thermal damage. An increase in the heater shell length improves the total heat transfer performance. Conventional heaters often only heat the bottom formation. Therefore, while optimizing the construction, it is vital to ensure that the weight of the heater itself does not exceed the tensile strength of the cable and consider shifting down the perforation outlet or lowering the outlet.